Study on Relationship between Socio-economic Status and Adoption Behaviour of Mandarin Growers of Upper Subansiri District of Arunachal Pradesh - N. K. Patra, Tanga Makcha, J. Longkumer, L. Y. Longchar; A. K. Makar (Indian Journal of Extension Education, 2023)
A study was conducted to know the ‘Adoption Behaviour Index’ of mandarin orange (citrus reticulata) growers of Arunachal Pradesh, India. In this study, 100 mandarin farmers from tribal community were purposively included as respondents from 5 selected blocks of Upper Subansiri distric of Arunachal Pradesh. Data were collected with the help of interview schedule. For analysis of data frequency, percentage, mean, standard deviation and correlation were followed. It was found that majority of the farmers of the study area had medium level of ‘adoption behaviour index’. Majority of the mandarin growers of the study area were aware about crop management and cultivation practices of mandarin cultivation but the adoption level were extremely low or even not adopted. Farmers of the study area were well acquainted with the extension agents but they were not accessing services and consultancies from government extension system regularly. Study also proves that socio-economic characteristics of mandarin growers such as education, Size of operational land holding, Accessibility of the village of the study area, Land under mandarin cultivation, Number of trees in the orchard, Material possession, Income from agricultural sector, Income from mandarin cultivation, Annual income, Source of communication, Extension Contact and Training exposure have positive and significant correlation with the ‘Adoption Behaviour Index’.